2018
DOI: 10.1186/s12943-018-0829-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MT1JP functions as a ceRNA in regulating FBXW7 through competitively binding to miR-92a-3p in gastric cancer

Abstract: BackgroundEmerging evidence has shown that dysregulation function of long non-coding RNAs (lncRNAs) implicated in gastric cancer (GC). However, the role of the differentially expressed lncRNAs in GC has not fully explained.MethodsLncRNA expression profiles were determined by lncRNA microarray in five pairs of normal and GC tissues, further validated in another 75 paired tissues by quantitative real-time PCR (qRT-PCR). Overexpression of lncRNA MT1JP was conducted to assess the effect of MT1JP in vitro and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
169
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(174 citation statements)
references
References 34 publications
1
169
0
Order By: Relevance
“…Previous references proved that MT1JP has been played a tumor suppressor gene in a lot of tumors (L. H. Liu, Yue, et al, 2016; Yang et al, ; G. Zhang et al, ; Zhu, Ma, et al, ). For instance, L. H. Liu, Yue, et al () first indicated that MT1JP expression was downregulated in the cancer tissues and downregulation expression of MT1JP promoted cancer cell deterioration and cancer formation through regulating p53 expression via interactions with the TIAR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous references proved that MT1JP has been played a tumor suppressor gene in a lot of tumors (L. H. Liu, Yue, et al, 2016; Yang et al, ; G. Zhang et al, ; Zhu, Ma, et al, ). For instance, L. H. Liu, Yue, et al () first indicated that MT1JP expression was downregulated in the cancer tissues and downregulation expression of MT1JP promoted cancer cell deterioration and cancer formation through regulating p53 expression via interactions with the TIAR.…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously, lncRNAs can modulate gene expression in human cancers by acting as ceRNAs. [26][27][28][29][30] Here, we designed mechanism experiments to detect whether ARAP1-AS1 can act as a ceRNA in BCa. The localization of ARAP1-AS1 was detected in BCa cells.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs and lncRNAs belong to noncoding RNAs and increasing evidence demonstrated that lncRNA can act as competing endogenous RNAs (ceRNAs) to regulate mRNA by binding their common miRNAs in various cancers. [17][18][19][20] These regulatory networks are widely involved in tumor occurrence, development, apoptosis, and drug resistance in GC. For instance, HOTAIR contributed to cisplatin resistance by regulating VEGFA and PIK3R2 via targeting miR-126 in GC.…”
Section: Introductionmentioning
confidence: 99%